Inkorporasi Kromium pada Khamir dan Kapang dengan Substrat Dasar Singkong yang Diberi Kromium Anorganik - W D Astuti; T Sutardi; D Evvyernie; T Toharmat (Faculty of Animal Science, Bogor Agricultural University, 2006)
Organic-chromium (Cr) has higher availability for animals than inorganic-Cr sources. One of organic-Cr sources known is fungi contained high Cr. This organic-Cr was incorporated to fungi protein. Information about the best fungi or microorganisms used in organic-Cr production is still limited. The objective of this experiment was to study organic-Cr production using different kinds of fungi as Cr carrier. Organic-Cr production was conducted in a 4x3 factorial completely randomized experimental design with 3 replications. Four fungi used as carriers in organic-Cr production as the first factor were Saccharomyces cerevisiae, Aspergillus oryzae, Rhizopus oryzae and